2021
DOI: 10.3390/jpm11060568
|View full text |Cite
|
Sign up to set email alerts
|

Salivary DNA Methylation as an Epigenetic Biomarker for Head and Neck Cancer. Part I: A Diagnostic Accuracy Meta-Analysis

Abstract: DNA hypermethylation is an important epigenetic mechanism for gene expression inactivation in head and neck cancer (HNC). Saliva has emerged as a novel liquid biopsy representing a potential source of biomarkers. We performed a comprehensive meta-analysis to evaluate the overall diagnostic accuracy of salivary DNA methylation for detecting HNC. PubMed EMBASE, Web of Science, LILACS, and the Cochrane Library were searched. Study quality was assessed by the Quality Assessment for Studies of Diagnostic Accuracy-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The outcomes of meta-regression analysis showed that sample type ( p = 0.128), sample size ( p = 0.349), and DNA methylation method ( p = 0.275) were not significant sources of heterogeneity. However, anatomic tumor location ( p = 0.002) and gene profiling ( p < 0.001) were, in fact, potential sources of heterogeneity in this study ( Table S1 —see Part I) [ 13 ]. As shown in Table S2 , significant heterogeneity was found in all subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes of meta-regression analysis showed that sample type ( p = 0.128), sample size ( p = 0.349), and DNA methylation method ( p = 0.275) were not significant sources of heterogeneity. However, anatomic tumor location ( p = 0.002) and gene profiling ( p < 0.001) were, in fact, potential sources of heterogeneity in this study ( Table S1 —see Part I) [ 13 ]. As shown in Table S2 , significant heterogeneity was found in all subgroups.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported that biomarker accuracy in the Chinese population is different from other countries. 71,72 Although a number of systematic reviews have examined the utility of saliva in the diagnosis of oral, head, and neck malignancies, [73][74][75][76][77][78][79] limited review studies on the use of salivary biomarkers for diagnosis of distant cancers, especially BC are available. 54 To the best of our knowledge, this is the first systematic review and meta-analysis evaluating the potential of salivary biomarkers in the diagnosis of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that some methylation profiles in saliva were similar to those in tissue [ 135 ]. Moreover, saliva can be collected in a noninvasive, cost-effective, fast, and reliable way [ 135 , 136 ]. Therefore, salivary biomarkers can be applied to early detection, prognosis, and therapeutic effect response of cancer.…”
Section: Other Dna Methylation-based Liquid Biopsies For Lcmentioning
confidence: 99%
“…In recent years, saliva-based liquid biopsy for cancer has received much attention [127][128][129][130][131][132]. Analyzing components of saliva can reflect genomic and epigenomic alterations involved in physiological and pathological processes, and thus reflecting a person's physical conditions [133][134][135]. Previous studies have suggested that some methylation profiles in saliva were similar to those in tissue [135].…”
Section: Saliva Dna Methylation-based Liquid Biopsy For Lcmentioning
confidence: 99%
See 1 more Smart Citation